Evaluación de la altura optima de poda de formación en el cultivo de mora de castilla (Rubus glaucus bent), en el cantón Pimampiro, provincia de Imbabura - Moreno Terán, Homero Leonel (2012)
The present investigation was made in the parish Mariano Acosta of the canton Pimampiro, county of Imbabura, using as genetic material a cultivation of Moorish of castilla already established of two years of plantation. The treatments were constituted by heights of it blunts of basal of 0,30; 0,60; 0,90; 1,20 and blunt of tips of basal, secondary and tertiary branches, around 1,50 m. the experimental design of Complete Blocks was used at random with three repetitions and five treatments, and the test of Multiple Ranges from Duncan to 5% of probability. They were carried out all the necessary agricultural works in the cultivation of Moorish of Castile for their normal development, as emergency of basal; height of basal; fructification pruning; watering; control of overgrowths; fertilization; control fitosanitario and it harvests.